The institution of Waqf as a model for poverty alleviation: lessons from Malaysia - Kadouf, Hunud Abia; Hussain, Faridah; Sulaiman, Saudah (2015)
In Islamic states, Muslims are encouraged to make waqf to help the poor and needy. Malaysia, in the modern era, has specific rules or formalities in the making process of a waqf , which differ from one state to another. Due to the dissimilar provisions of waqf law in different states in Malaysia, there is a problem of administering waqf land. This paper examines the importance of making a waqf and the importance of uniformity to be complied with by states in registering a valid waqf. Employing a qualitative research methodology and from the doctrinal and comparative approach to the procedural legal system in Malaysia, this paper analyses the procedural requirement for waqf for Muslims in Malaysia. This paper contends that since a court’s decision in refusing registering waqf land will be dependent on the procedure of administering waqf in different states, a uniform Enactment in Malaysia for the law on waqf would serve a rather useful function in protecting not only the waqf property, but also the beneficiaries and the poor Muslims in Malaysia. Waqf Enactments are not covered by the National Land Code 1965.